Association between endogenous sex steroid hormones and insulin-like growth factor proteins in US men - Papatheodorou, Stefania; Rohrmann, Sabine; Lopez, David S.; Bradwin, Gary; Joshu, Corinne E.; Kanarek, Norma; Nelson, William G.; Rifai, Nader; Platz, Elizabeth A.; Tsilidis, Konstantinos K. (My University, 2014)
Purpose Sex steroid hormone concentrations and insulin-like growth factor (IGF) proteins have been independently associated with risk of cancer, chronic diseases, and mortality. However, studies that evaluated the inter-relation between the sex hormones and IGF pathways have provided mixed results. We examined the association between endogenous sex hormones and sex hormone-binding globulin (SHBG) with IGF-1 and IGF-binding protein 3 (IGFBP-3) in a population-based sample of US men. Methods Data from 1,135 men aged 20 years or older participating in the third National Health and Nutrition Examination Survey (NHANES III) were analyzed. Weighted linear regression was used to estimate geometric means and 95 % confidence intervals for IGF-1 and IGFBP-3 concentrations by sex steroid hormones and SHBG after adjusting for age, race/ethnicity, body mass index, waist circumference, alcohol consumption, cigarette smoking, physical activity, diabetes, and mutually adjusting for other sex hormones and SHBG. Results No significant association was observed between sex steroid hormones, SHBG, and IGF-1 concentrations. Total estradiol (% difference in Q5 − Q1 geometric means −9.7 %; P-trend 0.05) and SHBG (% difference −7.3 %; P-trend 0.02) were modestly inversely associated with IGFBP-3. Total testosterone was modestly inversely associated with IGFBP-3 (% difference −6.2 %; P-trend 0.01), but this association disappeared after adjustment for total estradiol and SHBG (% difference 2.6 %; P-trend 0.23). Androstanediol glucuronide was not associated with IGFBP-3. Conclusions These findings suggest that there may be inter-relationships between circulating total estradiol, SHBG, and IGFBP-3 concentrations. Future research may consider these inter-relationships when evaluating potential joint effects of the sex hormones and IGF pathways.
Keywords: Testosterone; Estradiol; Sex hormone-binding globulin (SHBG); Insulin growth factor-1 (IGF-1); Insulin growth factor-binding protein 3 (IGFBP-3)